Engaging Native American High School Students in Public Health Career Preparation Through the Indigenous Summer Enhancement Program - Dreifuss, Heather M.; Belin, Kalvina L.; Wilson, Jamie; George, Shawndeena; Waters, Amber-Rose; Kahn, Carmella B.; Bauer, Mark C.; Teufel-Shone, Nicolette I. (Frontiers in Public Health, 2022)
Native American1 populations are systematically marginalized in the healthcare and public health workforce. One effective approach to reduce health disparities and improve health care delivery among Indigenous populations is to train more Native American health professionals who integrate academic and cultural knowledge to understand and influence health behaviors and perspectives. Diné College partnered with Northern Arizona University to develop the Navajo Native American Research Center for Health (NARCH) Partnership, funded by the National Institutes of Health. The high school component of the Navajo NARCH Partnership created the Indigenous Summer Enhancement Program (ISEP), a 1-week summer training program providing exposure to health careers and mentorship in pursuing public health careers for Native American high school students. ISEP utilizes the Diné Educational Philosophy (DEP), a Navajo conceptual framework to serve as the foundation of the program. In 2020–2021, due to COVID-19 restrictions, the DEP model had to be incorporated in the Navajo NARCH high school virtual program activities. ISEP used 2018 and 2019 past program evaluation data to inform the virtual programming. Students' perception of the program was collected using an online Qualtrics evaluation questionnaire. Students stated appreciation for program staff, fellow students, peer mentors and culturally relevant learning experiences in both virtual and in-person environments. Recommendations included: expanding the length of ISEP and continuing the hands-on activities and Public Health Leadership series.